Psychological Factors for the Prevention of Conflict Situations in Family Relationships - Qarshiboeva Gulnoza Abduqodirovna; Baratullayeva Dilnoza Habibullo qizi (Academia One Publishing, 2023)
the article reveals psychological factors for the Prevention of conflict situations in family relationships, in which it is stated that cases of Social Psychological disadaptation during adolescence in the family can lead to consequences that can seriously negatively affect the maturation of a teenage person if they are not resolved in a timely manner
Keywords: teenager; family; family relationships; educational sphere